Errors in aerial survey count data: Identifying pitfalls and solutions. Issue 3 (18th March 2022) - Davis, Kayla L.; Silverman, Emily D.; Sussman, Allison L.; Wilson, R. Randy; Zipkin, Elise F.
Abstract: Accurate estimates of animal abundance are essential for guiding effective management, and poor survey data can produce misleading inferences. Aerial surveys are an efficient survey platform, capable of collecting wildlife data across large spatial extents in short timeframes. However, these surveys can yield unreliable data if not carefully executed. Despite a long history of aerial survey use in ecological research, problems common to aerial surveys have not yet been adequately resolved. Through an extensive review of the aerial survey literature over the last 50 years, we evaluated how common problems encountered in the data (including nondetection, counting error, and species misidentification) can manifest, the potential difficulties conferred, and the history of how these challenges have been addressed. Additionally, we used a double‐observer case study focused on waterbird data collected via aerial surveys and an online group (flock) counting quiz to explore the potential extent of each challenge and possible resolutions. We found that nearly three quarters of the aerial survey methodology literature focused on accounting for nondetection errors, while issues of counting error and misidentification were less commonly addressed. Through our case study, we demonstrated how these challenges can prove problematic by detailing the extent and magnitude of potential errors. Using our online quiz, we showed that aerial observers typically undercount group size and that the magnitude of counting errors increases with group size. Our results illustrate how each issue can act to bias inferences, highlighting the importance of considering individual methods for mitigating potential problems separately during survey design and analysis. We synthesized the information gained from our analyses to evaluate strategies for overcoming the challenges of using aerial survey data to estimate wildlife abundance, such as digital data collection methods, pooling species records by family, and ordinal modeling using binned data. Recognizing conditions that can lead to data collection errors and having reasonable solutions for addressing errors can allow researchers to allocate resources effectively to mitigate the most significant challenges for obtaining reliable aerial survey data. Abstract : We highlight common challenges associated with collecting and analyzing aerial survey data to estimate abundance including nondetection, counting error, and species misidentification. Using a literature review, case study, and an online quiz, we explore the pros and cons of available solutions to overcome each issue. We conclude by providing specific suggestions for practitioners designing aerial surveys. This paper provides clarity on the possible errors that can be introduced in aerial survey data, guides researchers via reasonable approaches to address ongoing issues, and identifies areas for future research.